1985
DOI: 10.1039/c39850000441
|View full text |Cite
|
Sign up to set email alerts
|

A new diagnostic tool for elucidating the mechanism of enantioselective reactions. Application to the Hajos–Parrish reaction

Abstract: A dilution effect shows that the proline-catalysed Robinson cyclisation involves both enantioselective and non-enantioselective processes, with a different dependence on amino acid concentration.The Hajos-Parrish reaction1 presents a most interesting mechanistic problem in the field of enantioselective synthesis (Scheme l), but only indirect mechanistic studies have been carried out so far, mainly through structural modifications of the catalyst2 and/or the substrate.3 We report here direct

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The initial proposed mechanism [29] for the intramolecular aldol reaction involved the presence of two proline molecules, one forming the enamine nucleophile and other being a proton relay based on an observed small dilution effect [30] and a small nonlinear effect [31]. However, a careful repetition of those experiments showed that neither a dilution nor a nonlinear effect was present [32].…”
Section: Intramolecular Proposed Mechanismmentioning
confidence: 99%
“…The initial proposed mechanism [29] for the intramolecular aldol reaction involved the presence of two proline molecules, one forming the enamine nucleophile and other being a proton relay based on an observed small dilution effect [30] and a small nonlinear effect [31]. However, a careful repetition of those experiments showed that neither a dilution nor a nonlinear effect was present [32].…”
Section: Intramolecular Proposed Mechanismmentioning
confidence: 99%
“…[1 -7] Indeed, since the famous asymmetric annulation catalyzed by l-proline in 1970s, [8,9] reported by Hajos et al and Wiechert et al, almost nothing new was published, except some examples of intramolecular Michael additions catalyzed by a stoichiometric amount of l-proline. [10,11] In the 1980s, Agami [12,13] postulated a mechanism involving two molecules of l-proline based on non-linear effects in the formation of the Wielands ketone, but recent works of Houk and List 14 have contradict his results. Only recently, many examples of reactions catalyzed by l-proline were reported, such as aldol reactions, [14 -34] Mannich reactions, [35 -46] conjugate additions, [47 -50] a-aminations, [51 -54] a-aminooxylations, [55][56][57] a-alkylations [58] and related reactions.…”
Section: Introductionmentioning
confidence: 99%
“…176,177 As the computational chemistry is developed, the mechanism for (S)-proline-catalyzed aldol reaction is investigated. The Houk group shows evidence for the involvement of only one proline molecule in the transition states of intramolecular aldol reactions, which are based on kinetic measurements and the absence of nonlinear and dilution effects.…”
Section: Mechanistic Studiesmentioning
confidence: 99%